The Mesoproterozoic Maz terrane in the Western Sierras Pampeanas, Argentina, equivalent to the Arequipa-Antofalla block of southern Peru? : Implications for West Gondwana margin evolution - Casquet, César (2008)
The rocks of Sierra de Maz and Sierra del Espinal (Western Sierras Pampeanas) represent pre-Famatinian (Ordovician) basement. Isotope compositions (Nd and Pb) of metasedimentary rocks and SHRIMP U–Pb dating of detrital zircons, combined with other geological evidence, show that three parallel N–S domains can be recognized. The central Maz Domain contains pre-Grenvillian metasedimentary rocks deposited between 1.2 and 1.6 Ga, that underwent Grenvillian granulite facies metamorphism and were intruded by mafic igneous rocks and massif-type anorthosites. Metasedimentary rocks have high Nd TDM ages (1.7–2.7 Ga) and very radiogenic Pb (μ = 9.8–10.2), suggesting provenance from reworked early Proterozoic or Archean continental crust. The domains to the east and west of the Maz Domain consist of three metasedimentary sequences with Nd TDM ages between 1.2 and 1.6 Ga and variably radiogenic Pb (μ = 9.6–10.0). U–Pb SHRIMP dating of detrital zircons, Nd TDM model ages and comparison with other data suggest that these sequences are post-Grenvillian, i.e., Neoproterozoic and/or early Paleozoic. The Maz Domain is interpreted as a suspect terrane similar to the northern Arequipa–Antofalla craton that forms the basement of the Central Andes; both underwent Grenville-age orogeny and were probably once continuous along the western margin of Amazonia (West Gondwana).